PERUBAHAN SOSIAL BUDAYA PADA MASYARAKAT DAYAK MA’ANYAN DI DESA WARUKIN KECAMATAN TANTA KABUPATEN TABALONG (Studi Peranan Pendidikan) - Noor Herliana (JURNAL SOCIUS, 2015)
The aims of this research are to know: (1) society education conditions dayak maanyan (2) its happening process social change culturize with mark sense education (3) education role tu cultural social change. Observational location to be done at warukin’s village tanta’s district tabalong’ regency. This research utilize qualitative method. Data collecting rech with interview, observation, documentation and it affiliate. Informan determination with purposive and snowball sampling. This research finds first education has experienced step-up or progress experiences changing built by earlychildhood education and middle school. Before children doesn’t want school now child willingness comes in college, well at earlychildhood, primary school and middle. Both of happening changed process is talk shop society no longer undivided rely from their forest result be connected with swasta sector and governance sector, life that modestly is now beginning gently amends go to middleweight life and cultural appreciation be taught on  base rate education to keep up region culture to protage. Third play a part education at family as teaches and in dogma, get socialization with environmentally surrounding and more emphasizes to that child important education in future. Play a part education at schooled, as develops culture to read, write and gets computing and education material at studies by cognitive, afective and psycomotor. Play a part education at conjoined as deep partnership with side achooled as committee of school, following gets role in contribution lents fund, help and energy. Get starting point of this research finding, severally suggest one is proposed that is (1) increase society role in advance education (2) family role are expected get to help childs in formal education working out (3) for school, that aptly gets to utilize all kind help.Key word: changing social culture, Dayak Maanyan, education role